Ferulic Acid Protects Endothelial Cells from Hypoxia-Induced Injury by Regulating MicroRNA-92a - Yuqi Huang; Li Tian; Yan Liu; Jiangwei Liu; Jianzhao Huang (Applied Bionics and Biomechanics)
Background & Aim. Ferulic acid (FA), the main effective ingredient in Angelica sinensis, has been widely recognized as the cause of angiogenesis and proliferation of human umbilical vein endothelial cells (HUVECs). This study is mainly aimed at investigating the effect of FA on the apoptosis of HUVECs, which may play a key role in angiogenesis. Materials and Methods. CCK-8 (cell counting kit-8), Western blotting and Annexin V-FITC/PI staining were used to detect cell viability and apoptosis after hypoxia stimulation. The level of microRNA-92 a (miR-92 a) was detected by qRT-PCR.. Then, the assays of flow cytometry and the annexin V/PI staining kit were applied to value the impact of FA on hypoxia-induced cell proliferation, cell cycle distribution, and apoptosis. Furthermore, the inhibitor and mimic of miR-92a were also administrated to explore the role of miR-92a in this process. Student’s t-test was used to explore the differences between two groups, while one-way analysis of variance (ANOVA) was used to explore the differences between more than two groups. Results. The results showed that hypoxia stimulation significantly inhibited HUVEC viability and proliferation, such as remarkably decreasing the expression of CDK2, CDK4, and cyclin D1 in HUVECs. The results of annexin V-FITC/PI apoptosis detection showed that hypoxia culture significantly induced HUVEC apoptosis, which indicated that hypoxia stimulation significantly inhibited viability and proliferation of HUVECs but caused cell apoptosis and the expression of miR-92a. Meanwhile, FA remarkably protected HUVECs from hypoxia-induced inhibition of viability and proliferation, as well as the enhancement of apoptosis and miR-92a expression. Furthermore, suppression of miR-92a enhanced the protective effects of FA on hypoxia-induced HUVECs, while activation of miR-92a reversed those effects. Conclusion. Our study reported that FA preserved HUVECs from hypoxia-induced injury via regulating miR-92a, which facilitated the understanding of the protective capacity of FA in hypoxia-caused HUVEC injury.